Debt Guarantee Settlement Patterns in Minangkabau - Syukriah, H.G.; Yaswirman,; Hasan, Firman; Kurniawarman,; Taufiqurrahman, (International Journal of Criminology and Sociology, 2021)
Debt collateral is often unacceptable to the execution of debt collateral because there is coercion and leads to court so that many debts are not collected. In Minangkabau customary law, there is no compulsion to pay off debts. This research answers how people make debt-receivables agreements and must be repaid by the debtors in the Minangkabau customary law arrangement in Sungai Dareh village, West Sumatra. This research method is through observation and interviews of local customary leaders. The implementation of the pattern of execution of debt collateral settlement in Minangkabau is motivated by the legal relationship between the creditor and the collateral in the form of land. The creditor only has the right to cultivate or take the proceeds from the land given by the debt recipient until the debt is paid off or redeemed by the debt recipient, so that debt settlement will never transfer ownership rights to the land. In an urgent situation, the creditor can transfer the debt to the new lender, which stops the legal relationship between the first creditor and the debt recipient and creates a new legal relationship between the second creditor and the debt recipient. Creditors' rights remain a priority, and there is no time limit in paying off debts. This debt settlement is very different from debt settlement in positive law in Indonesia. The creditor has the right to sell the land as collateral for the debt if the debt cannot be settled after a certain period, which results in the loss of ownership of the debt recipient over the land that is used as debt collateral. There is a need for positive legal reform in Indonesia regarding the execution of debt guarantees.